Prenatal exposure to polycyclic aromatic hydrocarbons and blood pressure in the early life of children - Xiaodong Chen; Lingling Dong; Lina Yang; Yan Yang; Liyu Yang; Sijia Han (Ecotoxicology and Environmental Safety)
Exposure to polycyclic aromatic hydrocarbons (PAHs) has been associated with many adverse health outcomes. This cohort study investigates the association between prenatal exposure to PAHs and blood pressure in children aged 4–6 years. Conducted in Shenyang, China, the study includes 5642 children whose mothers provided urine samples in the third trimester, which were analyzed for PAH metabolites. Children’s blood pressure indicators, including systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and pulse pressure (PP), were measured during follow-up. Multivariable regression models, adjusted for key confounders, were used to explore associations between PAH metabolites and blood pressure. Additionally, we applied quantile g-computation (g-comp) and Bayesian kernel machine regression (BKMR) to assess the combined and interaction effects of multiple PAH metabolites. Prenatal exposure to specific PAH metabolites showed significant associations with blood pressure parameters. 2-hydroxynaphthalene, 3-hydroxyfluorene, 9-hydroxyphenanthrene, and 1-hydroxypyrene were positively linked to SBP. For DBP, 2-hydroxynaphthalene, 1-hydroxynaphthalene, and total PAH metabolites revealed strong associations. PP was significantly linked to 3-Hydroxyfluorene, while MAP showed consistent associations with 2-hydroxynaphthalene, 1-hydroxynaphthalene, 9-hydroxyphenanthrene, and 1-hydroxypyrene. G-comp analysis revealed significant associations between prenatal PAH exposure and increases in SBP, DBP, and MAP, with no effect on PP. BKMR showed no strong evidence for SBP or DBP but suggested potential positive associations for PP and MAP at higher exposure quantiles, indicating nuanced, exposure-dependent relationships with blood pressure outcomes. This study, being one of the first to explore these associations in children, provides important insights into the potential long-term health impacts of prenatal PAH exposure on childhood cardiovascular health.